Appointing Charity Directors in Response to ESG Incidents - Gertsberg, Marina; Jung, Hae Won (Henny); Zhang, Yuyang (Journal of Financial and Quantitative Analysis, 2026)
An abstract is not available for this content so a preview has been provided. Please use the Get access link above for information on how to access this content.